Association between Epicardial Adipose Tissue Thickness and Clinical and Metabolic Parameters in Patients with Psoriasis and Psoriatic Arthritis: A Cross-Sectional Study from Turkiye - Gurok, N. G.; Oz, B.; Ozturk, S.; Karaca, Y.; Yildirim, E.; Ulucan, B. G.; Karaca, A. D. (Wolters Kluwer Medknow Publications, 2026)
Background:Psoriasis and psoriatic arthritis (PsA) are chronic inflammatory diseases that affect not only the skin and joints but also the cardiovascular system.Aim:To investigate the relationship between epicardial adipose tissue (EAT) thickness and anthropometric measurements, laboratory parameters, and clinical variables in patients with psoriasis and PsA.Methods:This cross-sectional study included 65 patients with psoriasis vulgaris (with or without PsA) and 54 healthy controls. Demographic, clinical, and laboratory data of the participants were recorded. EAT, left ventricular end-systolic diameter (LVESD), left ventricular end-diastolic diameter (LVEDD), interventricular septum thickness (IVS), and ejection fraction (EF) were measured by echocardiography. Associations between EAT thickness and patient parameters were evaluated using Spearman correlation and multivariate linear regression analyses.Results:The mean ages of the patient and control groups were 43.88 +/- 13.1 years and 44.81 +/- 12.88 years, respectively. Low-density lipoprotein cholesterol, LVESD, and IVS were significantly higher in the control group compared with psoriasis patients (P = 0.021, P < 0.001, P < 0.001, respectively). C-reactive protein (CRP) levels (P < 0.001), systolic blood pressure (P < 0.001), diastolic blood pressure (P = 0.023), and EAT thickness (P < 0.001) were significantly higher in the patient group. Disease duration (P = 0.028) and PASI (P = 0.012) were significantly greater in psoriasis patients with PsA. EAT positively correlated with body mass index (BMI) (r = 0.307, P = 0.024), CRP (r = 0.344, P < 0.001), and systolic blood pressure (r = 0.185, P = 0.044).Conclusions:EAT thickness was higher in patients with psoriasis than in control participants. EAT positively correlated with BMI, CRP, and systolic blood pressure.
Keywords: Cardiovascular risk; epicardial adipose tissue; psoriasis; psoriatic arthritis